Pengaruh Time Budget Pressure Terhadap Perilaku Disfungsional Auditor dengan Mediasi Skeptisisme Profesional di KAP Provinsi Bali - Widiantari, Ida Ayu Made; Astika, Ida Bagus Putra (E-Jurnal Akuntansi; Vol 25 No 2 (2018)DO - 10.24843/EJA.2018.v25.i02.p04, 2018)
The existence of discrepancy between the time available with the time required to complete the audit task can affect the auditor's professional work. This research is done in all offices of Public Accounting Firm in Bali as many as nine offices located in the Region of Bali in 2017 by making auditors as much as 70 people as sample with saturated sample method. Data collection was done by distributing questionnaires with 52 respondents who returned and deserve to be used while 21 were aborted. Analytical technique used is path analysis technique. Based on the analysis, time budget pressure variable has a significant positive effect on dysfunctional behavior of auditors at Public Accounting Firm in Bali. Time budget pressure negatively affects the skepticism of auditor professionals at Public Accounting Firm in Bali. Skepticism of professional auditors negatively affects the dysfunctional behavior of auditors at Public Accounting Firm in Bali. Professional auditor skepticism mediates the positive influence of time budget pressure on dysfunctional behavior of auditors at Public Accounting Firm in Bali. Keywords: time budget pressure, professional skepticism of auditors, dysfunctional behavior of auditors.